Mutation of Genes Associated with Body Color, Growth, Intermuscular Bone, and Sex Differentiation in Onychostoma macrolepis Using CRISPR/Cas9 - Tian Gao; Feilong Wang; Qihui Wu; Lingyao Gan; Canbiao Jin; Li Ma; Deshou Wang; Lina Sun (Fishes, 2025)
Onychostoma macrolepis is not only a protected Cyprinid species in the wild but also an emerging commercial aquaculture fish in China. The objective of this research was to genetically modify the genes associated with commercial traits by CRISPR/Cas9 for the protection and utilization of the germplasm resources of O. macrolepis. To that end, one-cell stage embryos were obtained via hormone-induced ovulation and artificial insemination in O. macrolepis. Eight genes related to body color, growth, intermuscular bone, and sex differentiation were mutated in O. macrolepis using the CRISPR/Cas9 system by microinjection of gRNA/Cas9 mRNA. The optimal dose of gRNA/Cas9 mRNA was determined by injection of different concentrations of tyr (tyrosinase)-gRNA/Cas9 and examination of the mutation rate and hatching rate of embryos. Indels were detected by T7 endonuclease I digestion and Sanger sequencing. F0 mutants with high mutation rates were selected for phenotype analyses. Disruption of body color gene tyr, mpv17 (mitochondrial inner membrane protein MPV17), and csf1ra (colony-stimulating factor 1 receptor, a) resulted in obvious phenotype with decreased or even absence of melanophores, iridophores, and xanthophores, respectively. Mutation of mstnb (myostatin b) led to improved growth performance. Mutation of mc4r (melanocortin 4 receptor) led to no obvious phenotype. Mutation of runx2b (RUNX family transcription factor 2b) and bmp6 (bone morphogenetic protein 6) resulted in decreased or absence of intermuscular bones, as revealed by alizarin red S staining. Mutation of cyp19a1a (cytochrome P450, family 19, subfamily A, polypeptide 1a) resulted in ovarian degeneration as revealed by gonadal histological examination. Therefore, this study successfully obtained mutants with obvious phenotypes of genes associated with body color, growth, intermuscular bone, and sex differentiation by CRISPR/Cas9 in O. macrolepis.